Early induction of cytokine release syndrome by rapidly generated CAR T cells in preclinical models - Jamali, Arezoo; Ho, Naphang; Braun, Angela; Adabi, Elham; Thalheimer, Frederic B; Buchholz, Christian J (EMBO molecular medicine, 2024)
Cytokine release syndrome (CRS) is a significant side-effect of conventional chimeric antigen receptor (CAR) T-cell therapy. To facilitate patient accessibility, short-term (st) CAR T cells, which are administered to patients only 24 h after vector exposure, are in focus of current investigations. Their impact on the incidence and severity of CRS has been poorly explored. Here, we evaluated CD19-specific stCAR T cells in preclinical models. In co-culture with tumor cells and monocytes, stCAR T cells exhibited anti-tumoral activity and potent release of CRS-related cytokines (IL-6, IFN-γ, TNF-α, GM-CSF, IL-2, IL-10). When administered to NSG-SGM3 mice, stCAR T cells, but not conventional CAR T cells, induced severe acute adverse events within 24 h, including hypothermia and weight loss, as well as high body scores, independent of the presence of tumor target cells. Human (IFN-γ, TNF-α, IL-2, IL-10) and murine (MCP-1, IL-6, G-CSF) cytokines, typical for severe CRS, were systemically elevated. Our data highlight potential safety risks of rapidly manufactured CAR T cells and suggest NSG-SGM3 mice as sensitive model for their preclinical safety evaluation. Synopsis To make CAR T cells available to all patients, various strategies facilitating the manufacturing process are followed. Short-term (st) CAR T cells are administered shortly after exposure to lentiviral vector (LV) particles. Here, their preclinical safety was assessed ex vivo and in vivo. stCAR T cells contain residual vector components on their surface, in particular the vesicular stomatitis virus (VSV) glycoprotein NSG-SGM3 mice develop severe CRS-like symptoms rapidly after stCAR T cell administration Release of CRS-typical cytokines occurs in absence of tumor cells and is enhanced by monocytes The interplay between CAR and LV proteins is the main trigger for cytokine release To make CAR T cells available to all patients, various strategies facilitating the manufacturing process are followed. Short-term (st) CAR T cells are administered shortly after exposure to lentiviral vector (LV) particles. Here, their preclinical safety was assessed ex vivo and in vivo.